Analysis of Financial and Non-Financial Factors on Fixed Assets Revaluation in Banking Companies - Ahmad Rifai; Prihatni, Rida; Sumiati, Ati (First Ciera Publisher, 2023)
This research was conducted to find the influence of leverage, liquidity, fixed asset intensity, firm size, management ownership, and independent commissioners on fixed asset revaluation. The data used in this research is secondary data in the form of financial statements and annual reports obtained through the company's website or the Indonesia Stock Exchange (IDX). The population in this study were banking sector companies listed on the IDX in 2020 - 2022. The sample selection in this study used the purposive sampling technique and resulted in 44 companies as the sample studied. This research uses quantitative methods. The analysis technique used is descriptive statistical analysis and logistic regression analysis. The results of this research indicate that fixed asset intensity and company size have a positive effect on fixed asset revaluation. Meanwhile, leverage, liquidity, management ownership, and independent commissioners have no effect on fixed asset revaluation.